Diário de Bitita, de Carolina Maria de Jesus : saltando os muros da subalternidade - Rocha, Wesley Henrique Alves da (2019)
This dissertation analyzes Diário de Bitita work by afro-brazilian writer Carolina Maria de Jesus. The work belongs to the autobiographical genre of literature, in which the author narrates her childhood and part of adolescence. We aimed to verify how the author jumps the walls of subordination, against the white, male and middle class homogeneity (domination) of the literature. Carolina breaks with the structures of domination that underlie Brazilian society, although the elite was not so keen to hear it. Based on the hypothesis that social issues, that is, the historical-political context in which the narrative takes place, play a certain role in the construction of Diário de Bitita, making them intrinsic to the work, we seek to present the implications of such questions in the process of construction and reception of the work by the literate society. In addition, from Gayatri Chakravorty Spivak and Alejandro Reyes, we reflect on the situation of black women and their ability to speak/be heard. The analysis starts from the multidisciplinarity, trying to apprehend issues inherent to his work, since, according to Candido (2000), the various areas of knowledge complement the analysis and allowing a deepening in the historical, sociological and critical bases of the work under analysis (CANDIDO, 2000). For this, through social science theorists and literary criticism, we evoke the houses of Carolina, the diaspora (displacements), race, gender and social class as analytical categories that allowed us to glimpse how social relations and the structures of society influenced the construction of the author's narrative. This multidisciplinary reflexive exercise, proposed by Antonio Candido, allows us a more complete look at the work and studies of Afro-Brazilian literature.